Community Health Centers as Social Development Agents - I Made Indra P; Johanna Debora Imelda; Sari Viciawati Machdum (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Community Health Centers are responsible in their working areas in various aspects both in terms of prevention, detection, and response. They continue to carry out empowerment tasks in the community, research has a difficult because not many researchers have explored the role of Community Health Centers in social development. Some researchers only see Community Health Centers as a health service provider. The purpose of this study is to describe the Community Health Center as an agent of social development during the COVID-19 pandemic. The research used a qualitative research method conducted by field research. The research was conducted in the work area of the East Jakarta Health Office, Community Health Centers in Pulo Gadung. From the results of the study, it was found that the Community Health Centers carried out all indicators of social development so it could be concluded that the Community Health Centers was an agent of social development in Indonesia. The results also show that the description of health services during the Covid-19 pandemic at the Pulo Gadung Health Center is good with the implementation of health services with the Covid-19 service SOP and changes in service flow and the provision of infrastructure that supports health services during the Covid-19 pandemic. Keywords: Social Development, Community Health Centers, Covid-19